Contribution of AI to environmental sustainability governance in India and Peru: a comparative study - Garikapati, Kyvalya (2025)
Artificial Intelligence (AI) in India has the potential to play a key role in ensuring sustainability and sustainable development. AI applications can: (i) accelerate sustainable business practices and the energy transition, thereby helping reduce environmental impact; (ii) improve efficiency in the management of natural resources, such as water and fertilizers in agriculture, thus contributing to minimizing environmental impact; (iii) have a positive impact on the prediction and management of natural disasters, such as earthquakes and floods, enabling faster and more efficient responses; (iv) be used to identify and monitor endangered species, thereby supporting biodiversity conservation. In turn, AI in Peru can: (i) accelerate sustainable business practices and the energy transition, thus helping reduce environmental impact; (ii) be used for the efficient management of natural resources, such as water and fertilizers in agriculture, thereby helping minimize environmental impact; (iii) have a positive impact on sustainable mobility and the development of smart cities in Peru, thus contributing to addressing the environmental challenges we face. It is also important to highlight that AI governance has the potential to play a major role in the development of both countries, and its implementation should be accompanied by strong policies and principles that ensure its ethical and responsible use to minimize risks and harm. In this paper, the authors delve into this important issue by analyzing its impacts, advantages, disadvantages, differences, and similarities, in order to highlight the valuable lessons learned from this comparative experience. They also add to their study a perspective based on fundamental rights and interdisciplinarity.